Neuromuscular electrical stimulation improves swallowing initiation in patients with post-stroke dysphagia - Zhang, Yao-Wen; Dou, Zu-Lin; Zhao, Fei; Xie, Chun-Qing; Shi, Jing; Yang, Chen; Wan, Gui-Fang; Wen, Hong-Mei; Chen, Pei-Rong; Tang, Zhi-Ming (Frontiers in Neuroscience, 2022)
Objective More than half of post-stroke patients develop dysphagia, which manifests as delayed swallowing and is associated with a high risk of aspiration. In this study, we aimed to investigate the immediate effect of neuromuscular electrical stimulation (NMES) on swallowing initiation in post-stroke patients using videofluoroscopic swallowing study (VFSS) data. Materials and methods This randomized, self-controlled crossover study included 35 patients with post-stroke dysphagia. All selected patients received real and sham NMES while swallowing 5 ml of thin liquid. Participants completed the conditions in random order, with a 10-min interval between conditions. The primary evaluation indicators included the Modified Barium Swallow Impairment Profile-6 (MBSImp-6) and Penetration-Aspiration Scale (PAS). Secondary indicators included oral transit time (OTT), pharyngeal transit time (PTT), and laryngeal closure duration (LCD). Results Modified Barium Swallow Impairment Profile-6 (P = 0.008) and PAS (P < 0.001) scores were significantly lower in the Real-NMES condition than in the Sham-NMES condition. OTT (P < 0.001) was also significantly shorter during Real-NMES than during Sham-NMES. However, LCD (P = 0.225) and PTT (P = 0.161) did not significantly differ between the two conditions. Conclusion Neuromuscular electrical stimulation may represent a supplementary approach for promoting early feeding training in patients with post-stroke dysphagia. Clinical trial registration [https://clinicaltrials.gov/], identifier [ChiCTR2100052464].